GESCHLECHT UND GEWALT;DISKURSE, BEFUNDE UND PERSPEKTIVEN DER ERZIEHUNGSW (Schriftenreihe der Sektion Frauen- und Geschlechterforschung in der Deutschen Gesellschaft Für Erziehungswissenschaft (DGfE) Ser., 2020)
Although violence is a current and controversial subject in educational science, gender relations have so far not been addressed much in this context. The authors of the volume attempt to close this gap by examining the links between violence and gender in various social, political and pedagogical contexts and (social)pedagogical fields of action. In doing so, their focus lies on the different forms of violence and the functions of violence in maintaining the hierarchical heteronormative system of only two sexes.